Self-Determined Health App Evaluation Questionnaire Development: Mixed Methods Study - Angelika Rzepka; Kurt Edegger; Stefan Welte; Diotima Bertel; Anja Mandl; Günter Schreier (JMIR Human Factors)
Abstract BackgroundThe rapid increase in the number of health apps and their volatility in Austrian pp stores for Android and Apple are signs of a flourishing business sector in the wellness industry. ObjectiveIn this report, a questionnaire for informed decision-making by users was developed and evaluated using health apps in the categories “Nutrition”, “Exercise”, “Mental Health” and “Symptom Checker”. MethodsEvaluation criteria were derived from multiple reference documents and weighted in a survey, as well as a focus group meeting. Further, the selected evaluation criteria were tested against selected apps, which were most popular in the above-mentioned categories in fall 2023. ResultsThe short questionnaire is to be made publicly available to citizens and covers the categories of the quality of the app provider (regulatory compliance, safety, and quality assurance), the content quality of the app (functionality and evidence-based content), and the user-friendliness of the app. It consists of 6 question items, which appeared to be problematic in the evaluation most often. For ease of use, a short questionnaire with the most critical questions and helpful tips from the evaluation was expanded by the question of importance and with meaningful advice on how to find the right information in an app. ConclusionsThe evaluation based on the comprehensive questionnaire using selected apps confirmed the importance of such a questionnaire since most of the apps lacked basic properties in terms of safety and security.